Development of Thai Authentic Leadership Measure: An Application in a Military Context - and Bung-on Sorod, Iratrachar Amornpipat (Journal of Community Development Research (Humanities and Social Sciences), 2017)
The objectives of this present study are to investigate the constructs underlying of authentic leadership in the Thai context and to develop a reliable and valid measure of a Thai authentic leadership measure. Findings suggest that Thai authentic leadership and Walumbwa et al.’s (2008) authentic leadership models are found to be consistent in four dimensions: self-awareness, relational transparency, balanced processing, and internalised moral perspective. However, the effect of being collectivist in Thailand suggests an additional dimension of authentic leadership, namely, relational harmony. In order to develop a new scale, there were two parts included in this study. Part I included items development and factor determination, data collected from 172 Thai Armed Force Officers. An exploratory factor analysis determined five dimensional structural model with 21 items. In Part II, data collected from 400 Thai Navy Officers. A confirmatory factor analysis was performed. The Results suggested to delete two items, and five dimensional model (19 items) was acceptable fit to the data (RMSEA = 0.05; RMR = 0.02; CFI = 0.96; GFI – 0.93). This paper also discusses an agenda for future research and practical implications to develop the existing theory and authentic leaders in the Thai workplace.
Keywords: Authentic Leadership, Scale Development, Thailand, Military Context